2005
DOI: 10.1210/jc.2004-1512
|View full text |Cite
|
Sign up to set email alerts
|

Placental Expression of Substance P and Vasoactive Intestinal Peptide: Evidence for a Local Effect on Hormone Release

Abstract: The present study evaluated vasoactive intestinal peptide (VIP) and substance P (SP) mRNA expressions and the localization of both peptides in first- and third-trimester human placentas. VIP and SP mRNAs were detected by slot blot analysis in first- and third-trimester placental tissues. By immunohistochemistry both neuropeptides were localized in the trophoblast (syncytium and cytotrophoblastic cells) of the chorionic villi. Because little information is available on the role of VIP and/or SP on the secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 19 publications
3
43
0
1
Order By: Relevance
“…PAC1 receptor expression was detected in the same areas: stronger expression was described in stroma cells of the villi, while weaker expression in the trophoblast cells. Similar pattern of VIP immunoreactivity was detected by Marzioni and coworkers [43]. Immunostaining was present in both trophoblast layers and in the endothelium of the fetal vessels.…”
Section: Occurrence Of Pacap and Pacap Receptors In The Placentasupporting
confidence: 85%
“…PAC1 receptor expression was detected in the same areas: stronger expression was described in stroma cells of the villi, while weaker expression in the trophoblast cells. Similar pattern of VIP immunoreactivity was detected by Marzioni and coworkers [43]. Immunostaining was present in both trophoblast layers and in the endothelium of the fetal vessels.…”
Section: Occurrence Of Pacap and Pacap Receptors In The Placentasupporting
confidence: 85%
“…In human pregnancy, cytotrophoblast and syncytiotrophoblast cells of first and third trimester placenta express VIP and the same was reported in the trophoblast cell line JEG‐3 . VIP high affinity receptors on JEG‐3 cell line mediate hCG synthesis through CREs .…”
Section: Vip: An Emerging Candidate As a Pregnancy Regulatory Neuropesupporting
confidence: 57%
“…By means of an experimental approach to the human fetal-maternal interface, we showed the participation of endogenous VIP in the fetalmaternal interaction with a pro-implantatory role by increasing the expression of Treg markers and LIF (Fraccaroli et al 2009). Other authors have reported on the ability of VIP to modulate hCG and progesterone in human trophoblast cultures (Marzioni et al 2005) and to be selectively concentrated in the uterine vasculature, where its levels have been reported to be 2.5-fold greater than in maternal blood (Ottesen et al 1982).…”
Section: Discussionmentioning
confidence: 99%